Downregulation of PTP1B and TC-PTP phosphatases potentiate dendritic cell-based immunotherapy through IL-12/IFNγ signaling - Claudia Penafuerte; Matthew Feldhammer; John R. Mills; Valerie Vinette; Kelly A. Pike; Anita Hall; Eva Migon; Gerard Karsenty; Jerry Pelletier; George Zogopoulos; Michel L. Tremblay (OncoImmunology, 2017)
PTP1B and TC-PTP are highly related protein-tyrosine phosphatases (PTPs) that regulate the JAK/STAT signaling cascade essential for cytokine-receptor activation in immune cells. Here, we describe a novel immunotherapy approach whereby monocyte-derived dendritic cell (moDC) function is enhanced by modulating the enzymatic activities of PTP1B and TC-PTP. To downregulate or delete the activity/expression of these PTPs, we generated mice with PTP-specific deletions in the dendritic cell compartment or used PTP1B and TC-PTP specific inhibitor. While total ablation of PTP1B or TC-PTP expression leads to tolerogenic DCs via STAT3 hyperactivation, downregulation of either phosphatase remarkably shifts the balance toward an immunogenic DC phenotype due to hyperactivation of STAT4, STAT1 and Src kinase. The resulting increase in IL-12 and IFNγ production subsequently amplifies the IL-12/STAT4/IFNγ/STAT1/IL-12 positive autocrine loop and enhances the therapeutic potential of mature moDCs in tumor-bearing mice. Furthermore, pharmacological inhibition of both PTPs improves the maturation of defective moDCs derived from pancreatic cancer (PaC) patients. Our study provides a new advance in the use of DC-based cancer immunotherapy that is complementary to current cancer therapeutics.